Cryptocurrency with a Conscience: Using Artificial Intelligence to Develop Money that Advances Human Ethical Values - Gladden, Matthew E. (Annales. Etyka w Życiu Gospodarczym, 2015)
Cryptocurrencies like Bitcoin are offering new avenues for economic empowermentto individuals around the world. However, they also provide a powerful tool thatfacilitates criminal activities such as human trafficking and illegal weapons salesthat cause great harm to individuals and communities. Cryptocurrency advocateshave argued that the ethical dimensions of cryptocurrency are not qualitatively new,insofar as money has always been understood as a passive instrument that lacksethical values and can be used for good or ill purposes. In this paper, we challengesuch a presumption that money must be ‘value-neutral.’ Building on advances inartificial intelligence, cryptography, and machine ethics, we argue that it is possibleto design artificially intelligent cryptocurrencies that are not ethically neutral butwhich autonomously regulate their own use in a way that reflects the ethical valuesof particular human beings – or even entire human societies. We propose a technological framework for such cryptocurrencies and then analyse the legal, ethical, andeconomic implications of their use. Finally, we suggest that the development ofcryptocurrencies possessing ethical as well as monetary value can provide humanbeings with a new economic means of positively influencing the ethos and valuesof their societies.